Treacher Collins syndrome - Y Samata; K S Ganapathy; S Latha; B N Padmavathi (Wolters Kluwer Medknow Publications, 2008)
Treacher Collin's syndrome is a rare syndrome that is characterized primarily by defects of the structures derived from first and second branchial arches. It is a group of closely related defects of head and face; often hereditary/familial in pattern. We report a case of a 20 year old female patient who presented with features of this syndrome.